(untitled) (Global Journals of Research in Engineering, 2013)
Occurrence of faults in a power system causes transients which decrease transient stability of that system Superconducting fault current limiter SFCL is a promising solution to reduce and control this fault short circuit current which is inevitable to electric power systems due to growing interconnection of electrical power systems In this paper a simulated proof of the capability of SFCL in improving the system transient stability is revealed At first a SFCL model is designed using simulink Then that model is introduced in a so-called three phase system After that the system is taken under different fault conditions to investigate transient stability for each Finally it is shown from the simulation result that the system transient stability has improved